Penentuan Prioritas Kegiatan Perawatan Bangunan Gedung Sekolah Negeri Di Kota Blitar - Ismanto Ismanto; Harimurti Harimurti; Yulvi Zaika (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2017)
Performance of a building construction will decrease with increase life service of the structure. To maintain the performance building in order to remain functioning properly it is necessary to repair the damaged building components. The purpose of this study is to get an assessment the physical condition of the building and analyze damage level of school structure in Blitar City, and get the order to maintenance of elementary school structures in Blitar City. Weight of structure criteria assessed by the building expert and analyzed with Analytical Hierarchy Process (AHP) method, then the result of the weight is multiplied by the physical condition index obtained from the observation. Assessment of physical condition index of elementary school structure in Blitar city is 69.34%, it can be interpreted that the structure is in deterioration or damage but does not affect the overall structure of the building.